2015
DOI: 10.1371/journal.pone.0135438
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin Protects Cardiac Myocytes from Doxorubicin Toxicity by Sp1-Mediated Transactivation of Survivin

Abstract: Insulin inhibits ischemia/reperfusion-induced myocardial apoptosis through the PI3K/Akt/mTOR pathway. Survivin is a key regulator of anti-apoptosis against doxorubicin-induced cardiotoxicity. Insulin increases survivin expression in cardiac myocytes to mediate cytoprotection. However, the mechanism by which survivin mediates the protective effect of insulin against doxorubicin-associated injury remains to be determined. In this study, we demonstrated that pretreatment of H9c2 cardiac myocytes with insulin resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 54 publications
4
32
0
Order By: Relevance
“…31 As shown in Figure 5a, Dox caused an approximately 2.7-fold increase in intracellular ROS generation as monitored by DCF fluorescence, which was significantly decreased by SPRC ( P <0.01). Moreover, consistent with recent studies, 31, 32 Dox-treated cells revealed the release of proapoptotic mitochondrial protein cytochrome c into cytosol. In contrast, SPRC prevented Dox-induced cytochrome c release ( P <0.05; Figure 5b).…”
Section: Resultssupporting
confidence: 91%
“…31 As shown in Figure 5a, Dox caused an approximately 2.7-fold increase in intracellular ROS generation as monitored by DCF fluorescence, which was significantly decreased by SPRC ( P <0.01). Moreover, consistent with recent studies, 31, 32 Dox-treated cells revealed the release of proapoptotic mitochondrial protein cytochrome c into cytosol. In contrast, SPRC prevented Dox-induced cytochrome c release ( P <0.05; Figure 5b).…”
Section: Resultssupporting
confidence: 91%
“…This may be because, per our RTK phosphorylation arrays, ponatinib elicited the strongest compensatory increase in INSR/IGF1R phosphorylation among these three TKIs. We also observed reduced doxorubicin cytotoxicity after IGF1 and insulin pretreatment, suggesting that these growth factors might alleviate anthracycline cardiotoxicity in cardiomyocytes, corroborating other studies (27). Phosphorylation of RTKs such as ErbB2, ErbB4, EGFR2, and Axl was not significantly altered by VEGFR2/PDGFR-inhibiting TKIs, except by the known Axl inhibitor cabozantinib.…”
Section: Discussionsupporting
confidence: 92%
“…insulin down-regulated SUR2A. Insulin has been suggested to inhibit cardiomyocytes apoptosis [8] , protects H9c2 cells against doxorubicin toxicity [32] , and decrease the size of myocardial infarction in whole heart ischaemia-reperfusion model [33] . In contrast, it has been shown that insulin inhibits cardioprotection afforded by ischaemic preconditioning via Akt-dependent mechanisms [9] .…”
Section: Discussionmentioning
confidence: 99%